STUDY OF STRATEGIES FOR COPING WITH STRESSFUL SITUATIONS IN ADOLESCENTS IN A SITUATION OF UNCERTAINTY - Yurchuk, Svitlana (Personality and environmental issues, 2024)
The purpose of the article is to highlight the strategies for coping with stressful situations in adolescence in the face of uncertainty, which is becoming more and more pronounced in the current socio-economic environment. The study is based on the assumption that adolescence is a critical period in the formation of vital skills, including adaptive mechanisms necessary for an effective response to rapid changes and information pressure. The publication examines the concept of “coping”, which comes from the English to cope, and reveals its essence as a set of cognitive, emotional and behavioral strategies aimed at maintaining or restoring emotional balance. The emphasis is placed on the classic works of A. Lazarus and S. Folkman, who identified two key phases in the process of overcoming stress: primary appraisal and secondary appraisal. In the Ukrainian psychological tradition (T.M. Titarenko, S.D. Maksymenko, O.A. Kirnos, V.M. Bortnik), the role of socio-economic factors and support from family and environment in the formation of individual coping strategies is emphasized. The article emphasizes that adolescence is particularly susceptible to uncertainty, as it is at this time that the choice of profession, the establishment of personal guidelines, and the development of social skills and self-esteem take place. The researchers point out that increased levels of anxiety often provoke passive or emotionally oriented responses, the most prominent of which are avoidance and impulsive actions. At the same time, researchers emphasize the importance of constructive forms of coping (assertive behavior, seeking social support, careful planning), which improve social adaptation and reduce the risk of destructive consequences. At the same time, some authors (E. Frydenberg, S. Hobfall) distinguish between “prosocial” and “destructive” strategies, which allows for a better understanding of behavioral coping in adolescence. Cultural and gender factors are also emphasized: in collectivist societies, more attention is traditionally paid to mutual support, and in individualistic societies, to independence and internal locus of control. A separate aspect of the article is an analysis of the application of S. Hobfall's Conservation of Resources Theory, according to which the threat of losing resources (time, physical strength, finances, social contacts) can be a driving factor in the emergence of stress. It is emphasized that in adolescence, the deficit of these resources is particularly acute in coping behavior and can lead to aggressive manifestations or avoidance. To confirm the relevance of these provisions, the article presents the results of an empirical study using S. Hobfall's “Strategies for Coping with Stressful Situations (SACS)” methodology. It involved 120 young men aged 17-18 from Vinnytsia region. The results showed that impulsive-aggressive reactions and unique behavior are most pronounced, while assertiveness and the search for social support were moderate or insufficiently formed in a significant number of respondents. At the same time, it was found that about a third of young men still tend to have constructive patterns (assertive actions, cautious steps, social openness), which indicates the potential for targeted development of prosocial skills. The results of the study show that the uncertainty of the modern world, exacerbated by socio-economic transformations, puts an additional strain on the psyche of young people. Harmonious personal development requires not only internal resources (including self-esteem, emotional intelligence, and self-control), but also an appropriate family, educational, and social environment in which young people will have “beacons” to guide them. The authors of the article emphasize the importance of developing active, problem-oriented coping strategies that allow for quick adaptation to unstable conditions. In addition, meaningful coping has a positive effect, encouraging young men to realize their own identity and the meaning of life's challenges. From a practical perspective, the results of the study allow us to offer psychologists, teachers, and parents specific recommendations for developing such skills as constructive communication, effective emotional regulation, and finding support resources. All of this contributes to the formation of a more mature, confident and flexible personality capable of responding creatively to the challenges of uncertainty. Finally, the proposed conclusions and methods can be used to prevent maladaptive behavior and increase the stress resistance of young people, and the article itself provides a theoretical and empirical basis for further research in the field of age and educational psychology.